Risk Factor of Mortality Among Covid-19 Infected Doctor in East Java, Indonesia - Sutrisno Sutrisno; Achmad Chusnu Romdhoni; steven christian susianto; Muhammad Shoifi; Mohammad Hud Suhargono; Muhammad Yusuf; Siti Nur Faidah; Bambang Pudjo Semedi; Rahardian Indarto Susilo; Aries Budianto; Andy Darma; Kamal Musthofa; Rachmat Agung Widodo; Burhan Mahendra Kusuma; Fahrizal Rizky Muharram; Arya Satya Rajanagara; Muhammad Tidar Abiyu; Dimas Setyanto (Asian Journal of Health Research, 2022)
Introduction: The report of doctors who died with COVID-19 in Indonesia was high and influenced by several factors. This study examined COVID-19 infected doctors and mortality risk factors in East Java. Material and Methods: This observational cohort study was conducted among doctors infected with COVID-19 in East Java during March 2020-September 2021 and collected the COVID-19 infected doctors’ deaths report. Doctors received a questionnaire on the status of COVID-19, history of covid-19 infection, age, sex, type of doctor, type of specialization and resident, pregnancy, underlying disease and nutritional status. All data were described and potential risk factors’ association was analyzed. Results: We reported 2041 doctors infected with COVID-19. Majority of them (52,5%) was male, 162 doctors were more than 59 years old, 162 doctors (7,9%) were died and 41,4% was general practitioner. The odds ratio in each risk factor for mortality was older age doctors 15,468 (95% CI 10,587-22,601), male 6,128 (95% CI 3,906-9,614), general practitioner 2,461 (95% CI 1,769-3,423), doctors with underlying disease 39,842 (95% CI 23,077-68,798), Type II diabetes mellitus 82,504 (95% CI 42,767-159,162), cardiovascular disease 50,152 (95% CI 16,672-150,866), hypertension 19,425 (95% CI 10,528-35,840), Chronic Obstructive Pulmonary Disease 5,52 (95% CI 0,610-49,992), Asthma 2,091 (95% CI 0,626-6,986), Obesity 30.750 (95% CI 15,293-61,828) and Pregnant doctors 43.013 (95% CI 10.986-168.414) (p<0,05). Conclusion: Older age, male, general practitioner, doctors with underlying disease, cardiovascular disease, Type II diabetes mellitus, hypertension, chronic obstructive pulmonary disease, asthma, obesity, pregnant doctors had been mortality risk factors among COVID-19 infected doctors.